Literatura do que não existe mais : a literatura pós-guerra fria nos territórios das extintas República Democrática Alemã e Tchecoslováquia - Silva, Raquel Belisario da (2021)
Through this study, we seek to open a new space for literary discussion, with the appreciation of works little or not known in the Brazilian academic environment, such as those produced in (Central-) Eastern Europe. The general hypothesis raised to initiate this research is that the fictional narrative of Central-Eastern Europe, especially the writing in the first decade after the end of the communist dictatorship, has its own characteristics, as a specific historical phenomenon of a determined space, which extends beyond the new borders of the countries that currently exist. The main objective is – from the reading of fictional narratives by authors from the Czech Republic, Slovakia and Germany – to think critically about the representation, in these narratives, of life in territories whose geopolitical identities have been modified due to the fall of the socialist regime that lasted for more than forty years. Three points serve as a basis to this end: possible consequences of continued exposure to the authoritarian regime that falls apart; the loss (?) of national identities from the break with the past; and the constitution of new forms of being a subject, when “what ceased to exist” was not only the time lived under an authoritarian regime, but also the spaces in which people had been born and lived until then. It is also proposed to look at how the authors write about the frontiers that have ceased to exist and the new territories constituted thereafter. In the selected works – Adam and Evelyn, by Ingo Schulze, No Saints or Angels, by Ivan Klíma, and Samko Tále's Cemetery Book, by Daniela Kapitáňová –, it is possible to verify aspects of the lives of ordinary people who need to adapt to new political realities and a new territorial division of their countries, while facing personal issues, such as death, affective and family relationships, professional career. In addition, there are traces of the past that promote constant transformations in the identities of the peoples of these spaces, composing different subjectivities within different collectivities. The theoretical foundation is based on a large constellation of studies regarding individual and collective memories, as well as the uses of historical memory and programmed forgetting, in the narratives of the formation of national and cultural identities, discussions revived by Aleida Assmann, Paul Ricoeur, Tzvetan Todorov, among others. The relationship between national identity and the constitution of the characters’ subjectivities, linked to the emergence of new identity constructions, is also debated here, with greater prominence to the sociosemiotics of Eric Landowski and the notion of ressentiment according to Max Scheler and Marc Angenot. There is also a briefly presented debate about the studies of post-socialist narratives, conducted by Madina Tlostanova, Dobrota Pucherová, Cristina Sandru, Dorota Kołodziejczyk, who revisit postcolonial theories, as well as Bakhtin’s chonotopes related to the post-communist tempo-localities. Finally, the condition of the literature before and after 1989 is contrasted in order to demonstrate whether the initial hypothesis was proven.